Hospitalization costs and their determining factors among patients undergoing kidney transplantation: a cross-sectional descriptive study - Maynara Fernanda Carvalho Barreto; Mara Solange Gomes Dellaroza; Karen Barros Parron Fernandes; Paloma de Souza Cavalcante Pissinati; Maria José Quina Galdino; Maria do Carmo Fernandez Lourenço Haddad (São Paulo Medical Journal, 2020)
ABSTRACT BACKGROUND: Cost evaluation is a key tool in monitoring expenditure for budget management. It increases the efficiency of possible changes through identifying potential savings and estimating the resources required to make such changes. However, there is a lack of knowledge of the total cost of hospitalization up to the clinical outcome, regarding patients admitted for kidney transplantation. Likewise, there is a lack of data on the factors that influence the amounts spent by hospital institutions and healthcare systems. OBJECTIVES: To describe the costs and determining factors relating to hospitalization of patients undergoing kidney transplantation. DESIGN AND SETTING: Cross-sectional descriptive study with a quantitative approach based on secondary data from 81 patients who were admitted for kidney transplantation at a leading transplantation center in southern Brazil. METHODS: The direct costs of healthcare for patients who underwent kidney transplantation were the dependent variable, and included personnel, expenses, third-party services, materials and medicines. The factors that interfered in the cost of the procedure were indirect variables. The items that made up these variables were gathered from the records of the internal transplantation committee and from the electronic medical records. The billing sector provided information on the direct costs per patient. RESULTS: The estimated total cost of patients’ hospitalization was R$ 1,257,639.11 (US$ 571,010.44). Out of this amount, R$ 1,237,338.31 (US$ 561,793.20) was paid by the Brazilian National Health System and R$ 20,300.80 (US$ 9,217.24) by the transplantation center’s own resources. The highest costs related to the length of hospital stay and clinical complications such as sepsis and pneumonia. CONCLUSIONS: The costs of hospitalization for kidney transplantation relate to the length of hospital stay and clinical complications.